Analysis of Land Use Change Using Landsat Imagery and GIS in West Cikarang District - Luthfiyah Khairun Nisa; Siti Dahlia; R Tricahyono Nur Harsono; Agung Adiputra (JPG (Jurnal Pendidikan Geografi), 2023)
The research was conducted in West Cikarang Subdistrict which was motivated by the large number of industrial areas which resulted in many agricultural to non-agricultural land uses changing. Based on this, the objectives of this study are 1) To determine the extent of land use change in West Cikarang District, Bekasi Regency in 2010-2020 using Landsat Imagery and GIS; 2) To determine the land use change in 2010-2020 in the West Cikarang District area of Bekasi Regency. The images used are Landsat images in 2010, 2015, and 2020. In this research, the method used is Supervised Image Classification for interpretation. This research uses a composite of bands 4,3,2 for Landsat 8 imagery and 3,2,1 for Landsat 7 imagery. This research uses a descriptive type of research, the method used in this research is a spatial approach. The Kappa accuracy produced in this research is 93.1%. The results of this land use change research that increased significantly were settlements, in 2010 residential land use had an area of 1660.1 Ha, in 2015 the use increased to 2227.8 Ha, and in 2020 residential land use increased again to 2285.3 Ha.Â Â